FOREIGN DIRECT INVESTMENT DETERMINANTS IN THE MANUFACTURING SECTORS IN MALAYSIA - Tsen, Wong Hock (PEOPLE: International Journal of Social Sciences, 2019)
Foreign direct investment (FDI) is a vital driver for economic growth in a country. Hence, FDI determinants should be identified in order to promote FDI. FDI could stimulate economic growth and economic growth could attract FDI. This study examines foreign direct investment (FDI) determinants in the main manufacturing sectors and the impact of FDI on economic growth in Malaysia. Moreover, this study examines the link between FDI and real national income. The vector error correction model (VECM) is used to estimate FDI determinants and the link between FDI and real national income. The results of the vector VECM show that the coefficients of real exchange rate are found to have positive impact on FDI. The coefficients of real national income, trade openness and real infrastructure are mostly found to have positive impact on FDI whilst the coefficients of real average wage and financial development are mostly found to have negative impact on FDI. Autocracy and polity are found to be significant determinants for many manufacturing sectors in the short run. Inflation is found to influence negatively FDI in the transport equipment sector. The Asian financial crisis, 1997-1998 is found to have influential impact on FDI in the petroleum products sector and the chemical and chemical products sector. These findings reveal that FDI determinants are not exactly the same for all the manufacturing sectors. Therefore, FDI would be attracted through a variety of policies. FDI is found to Granger cause real national income for the basic metal products sector and the chemical and chemical products sector whilst real national income is found to Granger cause FDI for the petroleum products sector. These findings demonstrate that FDI and economic growth are closely related. FDI can sustain economic growth in Malaysia. FDI is crucial for economic growth.